پێوه‌ندیی گێڕانه‌وه‌ به‌ ڕووداو و زمانه‌وه‌ له‌ ڕۆمانی: (داگیركردنی تاریكی)ی به‌ختیارعه‌لیدا (ئه‌م توێژینه‌وه‌یه‌ به‌شێكه‌ له‌ نامەی ماسته‌ر) - حسن, مه‌ریوان عمر; صاڵح, دیمه‌ن عبدالله (Sulaimani Journal for Humanities, 2022)
Narrative has a high degree in literature, because everything that is conveyed to the reader is done through narrative, and then events has(play) a major role and main relationship. In narrative, of course, the narrative of events by novelists have their own style, but narrative has a long history, we can say that it is much older than history, we can say that events become the essence of narratives, at the same time language plays an influential role. Because what is narrated because of language, if there is no means like language to narrative, it will be very difficult to deliver to the reader and the narrative is not done, so language becomes the hero of the novel and gives it pleasure , However, language is a rule of thumb in narrative, which is more an emphasizes on how the narrator tells the event(story). Therefore, language and events are one of the most important things in the novel during the narrative.
Keywords: Narration; Events; Novel Bekhtyar Ali